Strengthening the competence of junior high school social studies teachers in Klaten Regency in the implementation of deep learning - Anik Widiastuti; Raras Gistha Rosardi; Happri Novriza Setya Dhewantoro; Ahmad Muzakkil Anam (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2026)
Education plays a central role in shaping individual character and skills, especially amid the increasingly complex challenges of globalization. Meanwhile, in the context of Social Studies learning at the Junior High School level, the current approach still prioritizes memorization and data mastery without being balanced by the development of critical and analytical thinking skills. The deep learning approach has emerged as a solution to improve the quality of IPS education. This approach encourages students to understand concepts in depth and contextualize them with real-life situations. Teachers play a key role in the successful implementation of deep learning in IPS education, so they must understand what deep learning is and how to apply it. This community service program was organized to enhance the understanding and practical skills of Social Studies teachers at the Junior High School level in Klaten Regency. The method used in this program is a participatory and collaborative approach involving the Social Studies Teacher Forum (MGMP) through workshops and hands-on training. The results of this activity show an increase in teachers' understanding of the deep learning concept and their ability to design IPS learning at the SMP level using a deep learning approach.